2016
DOI: 10.3390/molecules21040545
|View full text |Cite
|
Sign up to set email alerts
|

Selenium in Cattle: A Review

Abstract: This review article examines the role of selenium (Se) and the effects of Se supplementation especially in the bovine species. Selenium is an important trace element in cattle. Some of its roles include the participation in the antioxidant defense the cattle farms. The nutritional requirements of Se in cattle are estimated at 100 µg/kg DM (dry matter) for beef cattle and at 300 µg/kg DM for dairy cows. The rations high in fermentable carbohydrates, nitrates, sulfates, calcium or hydrogen cyanide negatively inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
160
1
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(180 citation statements)
references
References 108 publications
(167 reference statements)
5
160
1
14
Order By: Relevance
“…The 9% decrease of concentration of Se in blood serum of cows (the concentration of Se on day 195 of pregnancy established as 100%) during the last trimester of pregnancy stated in this experiment indicated that Se-deficient cows provide Se to the detriment of their health to ensure adequate intake of the fetus and the newborns, while at the same time their own Se status has been reduced. These data confirm the results that an efficient Se transfer occurs from the pregnant animal to newborns, even in situations of low concentration of the element in the parent (Hefnawy et al 2014;Mehdi and Dufrasne 2016). The results of the present study also showed that under the conditions of selenium deficiency in the diet, despite cow-mother effort, the concentration of Se in blood serum of the calf was found to be by 48% lower than the approved reference values for the newborn calf (estimated as 100%).…”
Section: Diet-cow Se Transfer Efficiencysupporting
confidence: 75%
See 1 more Smart Citation
“…The 9% decrease of concentration of Se in blood serum of cows (the concentration of Se on day 195 of pregnancy established as 100%) during the last trimester of pregnancy stated in this experiment indicated that Se-deficient cows provide Se to the detriment of their health to ensure adequate intake of the fetus and the newborns, while at the same time their own Se status has been reduced. These data confirm the results that an efficient Se transfer occurs from the pregnant animal to newborns, even in situations of low concentration of the element in the parent (Hefnawy et al 2014;Mehdi and Dufrasne 2016). The results of the present study also showed that under the conditions of selenium deficiency in the diet, despite cow-mother effort, the concentration of Se in blood serum of the calf was found to be by 48% lower than the approved reference values for the newborn calf (estimated as 100%).…”
Section: Diet-cow Se Transfer Efficiencysupporting
confidence: 75%
“…In the 1960s, white muscle disease was diagnosed in young ruminants for the first time, and it was caused by the severe deficiency of Se (Muth et al 1958). Later, the results of the study carried out on cattle have shown that Se supplementation in Se-deficient cows has positive impact on their fertility, immune function, and growth and strengthening of the immune system (reviewed by Mehdi and Dufrasne 2016). The deficiency of Se is especially critical for dams during late pregnancy, when the transfer of Se to doi: 10.17221/86/2016-CJAS the fetus occurs even when dams are deficient in Se (Enjalbert et al 1999;Hefnawy et al 2014).…”
mentioning
confidence: 99%
“…Another possible limitation of the present study concerns the quantification of macronutrients and micronutrients in the various organic groups. Food composition tables generally do not account for differences in organic origin (except for specialty products, which were included in our FFQ to also cover organic and 'alternative' products), although a few observations suggest that at least some organic food products may contain different levels of several nutrients (20)(21)(22)(23)(24)(25)(26)(27)(28) . Since the generalizability of these differences in nutrient content remains uncertain and most of the observed differences were minor, they are, however, not likely to have strongly influenced our calculations.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…Dostopnost selena v zadostnih količinah v prehrani živine zagotavlja normalno delovanje njihovega imunskega sistema in reprodukcije. Večje vsebnosti selena v krmi posredno vplivajo tudi na večje koncentracije le-tega v mleku in mesu, ki ga zaužije človek (Mehdi & Dufrasne 2016).…”
Section: Selen V Gojenih Rastlinahunclassified